Analytical Review of Interest for Big Data - GORLEVSKAYA, L. E.; SEKERIN, V. D.; GUSOV, A. Z.; GOROKHOVA, A. E. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
High importance and great power of Big Data in connection with the lack of common understanding of the term has led to multiple challenges in the field. In order to overcome some of the challenges this study appeals to the Big Data term and presents an overview of approaches to Big Data. Authors argue that volume is the key characteristic of Big Data and suggest making the definition which is clear to a wide audience. This paper determines modern trends of interest for Big Data from different economy participants. It shows that the Big Data term has become mature. The paper proves high steady interest to the topic in science, business, society, government. General research of Big Data passed to research of different Big Data segments by key issues, technologies or applied industries.